P-256 Designing an e-ELCA learning path for specialists in palliative care. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Kitchen, Richard; Curran, Emily
Abstract : Background: e-ELCA (end of life care for all) is an e-learning programme from e-Learning for Health, delivering palliative and end of life care education. It was originally developed to support the Department of Health's End of Life Care Strategy, being designed to deliver education to the wider NHS workforce. More recently, there has also been a focus on offering educational opportunities to specialists in palliative care. Of note, e-ELCA is comprised of over 160 sessions and utilises 'learning paths' to allow users to identify sessions that will be helpful for their learning. Aim: To design an e-ELCA learning path for specialists in palliative care. This would allow this group to easily identify e-ELCA sessions that are relevant for their own learning. Methods: The JRCPTB (Joint Royal College of Physicians Training Board, 2014) speciality training curriculum for palliative medicine is used in the training of palliative medicine specialty registrars. The curriculum contains many sections including physical care, communication and ethics. Educational resources that support this curriculum will be helpful for registrars, but are also likely to be relevant for other specialists in palliative care. Therefore, e-ELCA sessions were mapped to the JRCPTB speciality training curriculum for palliative medicine (2010 with amendments 2014)1. This process was carried out by a specialty registrar in palliative medicine, with this work then reviewed by the e-ELCA clinical lead. Results: Initially 34 e-ELCA sessions were identified that mapped to the curriculum. Following further review, 10 of these were deemed to too basic in content for specialists in palliative care. The 24 sessions that remained comprised the final version of the learning path. This is now available on the e-ELCA website. Conclusions: The JRCPTB speciality training curriculum for palliative medicine was used to identify e-ELCA sessions that specialists in palliative care could use for their own education.